2007
DOI: 10.1176/appi.ps.58.4.521
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of Aggressive Acts Committed by Chronically Assaultive State Hospital Patients

Abstract: These findings indicate that assaultive behavior among state hospital inpatients is complex and heterogeneous. Because each type of assault requires a different management approach, characterizing aggressive behavior may be important in determining which institutional programs and treatment-plan interventions to implement when addressing inpatient aggression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 0 publications
4
37
0
Order By: Relevance
“…The focus on in-prison violence and the ability to separate control delusions as individual symptoms most likely explain why these findings differ from those of Duncan and colleagues (2008), which found no yy relationship between violence and hallucinations. However, even among psychotic persons, it remains likely that most aggressive behavior will result from ''adverse interpersonal interactions,'' such as arguments, rather than internal stimuli such as commanding auditory hallucinations (Quanbeck et al, 2007). Phobic-type symptoms appear to have reduced the likelihood of acting out.…”
Section: Discussionmentioning
confidence: 99%
“…The focus on in-prison violence and the ability to separate control delusions as individual symptoms most likely explain why these findings differ from those of Duncan and colleagues (2008), which found no yy relationship between violence and hallucinations. However, even among psychotic persons, it remains likely that most aggressive behavior will result from ''adverse interpersonal interactions,'' such as arguments, rather than internal stimuli such as commanding auditory hallucinations (Quanbeck et al, 2007). Phobic-type symptoms appear to have reduced the likelihood of acting out.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of aggressive acts among civilly committed inpatients showed that the most common type of aggression was impulsive (54%), even though most patients suffered from a psychotic disorder (Quanbeck et al, 2007). Using the method developed by Stanford and Barratt (1992), the investigators systematically described and then categorized aggressive acts as impulsive, organized (corresponding to Barratt's premeditated aggression), and psychotic (secondary aggression due to psychotic symptoms).…”
Section: Inpatients Who Assault While In the Hospitalmentioning
confidence: 99%
“…Three primary motivations for assault were described: impulsive-an assault committed in response to an immediate provocation and associated with agitation and loss of emotional control; planned-a controlled assault committed for a specific goal; and psychotic-assaults committed as a consequence of delusions, hallucinations, and/or disordered thinking. In recent work using the same categorization scheme, impulsive/reactive assaults comprised the largest number of observed incidents of aggression (46%; Quanbeck et al, 2007). As such, it should not be surprising that the PCL-R is not as strongly related to this type of aggression.…”
mentioning
confidence: 97%
“…Because previous research has indicated that impulsive aggression is the type of misconduct most often observed in psychiatric settings (Quanbeck et al, 2007), it may be that only certain aspects of the measures of psychopathy are associated with this type of aggression, such as factors measuring impulsive lifestyle. Additionally, measures of psychopathy may be most associated with aggressive incidents over a longer time period, whereas psychiatric symptoms may be more associated with imminent aggression; that is, aggression exhibited in the days or weeks after an assessment, rather than years.…”
mentioning
confidence: 99%